2005
DOI: 10.1210/me.2004-0434
|View full text |Cite
|
Sign up to set email alerts
|

The Pregnane X Receptor Regulates Gene Expression in a Ligand- and Promoter- Selective Fashion

Abstract: Recent studies have revealed that pregnane X receptor (PXR) can function as a master regulator to control the expression of phase I and phase II drug-metabolizing enzymes, as well as members of the drug transporter family, including multiple drug resistance (MDR) 1, which has a major role in multidrug resistance. Previously, we have demonstrated that steroid/xenobiotics metabolism by tumor tissue through the PXR-cytochrome P-450 3A (CYP3A) pathway might play an important role in endometrial cancer. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 36 publications
2
96
1
2
Order By: Relevance
“…1, 3B, and 4). We hypothesize that this discrepancy can be explained considering the report of Masuyama et al (2005), who demonstrated a ligand-and promoter-specific fashion of PXR-mediated transcription of CYP3A4 and MDR1 genes.…”
Section: Valproic Acid Induces Cyp3a4 and Mdr1 Via Pxr And Carmentioning
confidence: 91%
“…1, 3B, and 4). We hypothesize that this discrepancy can be explained considering the report of Masuyama et al (2005), who demonstrated a ligand-and promoter-specific fashion of PXR-mediated transcription of CYP3A4 and MDR1 genes.…”
Section: Valproic Acid Induces Cyp3a4 and Mdr1 Via Pxr And Carmentioning
confidence: 91%
“…We only focused on drug metabolism, but the full spectrum of drug disposition, including a growing list of transporters that influence drug absorption, distribution, and excretion should also be taken into account. Expression of CYP450 is also regulated by other genes such as PXR and CAR [11,14,15]. The outcome may also be influenced by the polymorphisms of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CYP3A4, PXR-dependent activation of P-gp by rifampin has been demonstrated [32] . PXR can also be activated by several chemotherapeutic agents, including paclitaxel [23] and cisplatin [54] . Synold et al showed that paclitaxel-activated hPXR induced hepatic expression of CYP3A4 and CYP2C8, as well as MDR1 expression in intestinal tumor cells resulting in enhanced metabolism of paclitaxel by CYP3A4 and CYP2C8, and excretion from the intestine via P-gp.…”
Section: Implications Of Pxr In Ddismentioning
confidence: 99%